2004
DOI: 10.1002/gepi.10304
|View full text |Cite
|
Sign up to set email alerts
|

Power of non‐parametric linkage analysis in mapping genes contributing to human longevity in long‐lived sib‐pairs

Abstract: This report investigates the power issue in applying the non-parametric linkage analysis of affected sib-pairs (ASP) [Kruglyak and Lander, 1995: Am J Hum Genet 57:439-454] to localize genes that contribute to human longevity using longlived sib-pairs. Data were simulated by introducing a recently developed statistical model for measuring marker-longevity associations [Yashin et al., 1999: Am J Hum Genet 65:1178-1193, enabling direct power comparison between linkage and association approaches. The non-parametri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…On the whole, the novel design resulted in more complexity and less efficiency in revealing gene-longevity associations in comparison with classic non-parametric approaches. 32,33,37 In conclusion, the ECHA study failed to evidence differences of IBD haplotype sharing in cousin-pairs born from concordant and discordant sib-pairs. It is likely that a larger sample size was required.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…On the whole, the novel design resulted in more complexity and less efficiency in revealing gene-longevity associations in comparison with classic non-parametric approaches. 32,33,37 In conclusion, the ECHA study failed to evidence differences of IBD haplotype sharing in cousin-pairs born from concordant and discordant sib-pairs. It is likely that a larger sample size was required.…”
Section: Discussionmentioning
confidence: 77%
“…However, despite the strong phenotypic selection, the results of IBD analyses did not reveal significant differences between concordant and discordant families. These negative findings, which contrast with the significant gene-longevity associations found by case -control studies, are most likely explained by sample sizes inadequate to reveal small genetic effects, 33 which are further smoothed when searched in the children of the probands and their cousins (one generation away from the one selected). A further confusing effect may have been played by TRD, which has been observed in our samples for both the studied chromosomal regions.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…[59] studied the efficiency of the ASP approach and found that the method is powerful in mapping rare recessive genes but has very low power in locating dominant genes. Tan et al [60] reevaluated the power issue of the method in longevity study and reported that a sample size of over 600 long-lived pairs (centenarians and their siblings over age 90)…”
Section: Linkage Analysismentioning
confidence: 99%
“…The small proportion of the extremely long-lived ASPs is more genetically selected than the majority who are just above the threshold. This is also indicated by the increased IBD sharing at older ages in the region harboring a beneficial gene [60]. It should be possible to increase the power of non-parametric linkage by introducing an optimal weighing scheme to the sharing for each pair based on a function of their ages.…”
Section: Linkage Analysismentioning
confidence: 99%